2007
DOI: 10.1007/s10875-007-9125-8
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Polymorphisms of Interleukin-17A and Interleukin-17F Genes on the Susceptibility to Ulcerative Colitis

Abstract: We investigated the association between ulcerative colitis (UC) and polymorphisms of IL-17A (rs2275913, G-197A) and IL-17F (rs763780, 7488T/C) genes. We employed the multiplex PCR-SSCP method to detect gene polymorphisms. Both the numbers of -197A (IL-17A) and 7488T (IL-17F) alleles were significantly correlated to the development of UC. The frequencies of -197A/A and 7488T/T genotypes in the UC group were significantly higher than those in the non-UC group. An adjusted analysis revealed that -197A and 7488T a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
112
2
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(121 citation statements)
references
References 30 publications
5
112
2
2
Order By: Relevance
“…This might explain why there was no GG Genotype to be found in this study. Similar to this study, Arisawa et al showed that G allele has been associated with protective effects in Asian patients with inflammatory and autoimmune conditions (Arisawa et al, 2007;Arisawa et al, 2008). But in present study, the findings suggest that IL-17F 7488G allele is associated with increased lung cancer risk in the Tunisian population (Kaabachi et al, 2014).…”
Section: Discussionsupporting
confidence: 81%
“…This might explain why there was no GG Genotype to be found in this study. Similar to this study, Arisawa et al showed that G allele has been associated with protective effects in Asian patients with inflammatory and autoimmune conditions (Arisawa et al, 2007;Arisawa et al, 2008). But in present study, the findings suggest that IL-17F 7488G allele is associated with increased lung cancer risk in the Tunisian population (Kaabachi et al, 2014).…”
Section: Discussionsupporting
confidence: 81%
“…[30][31][32][33][34][35] Recent reports have shown association of SNPs in the IL-17 gene with autoimmune diseases such as rheumatoid arthritis and ulcerative colitis. [36][37][38][39] The promoter SNP of the IL-17 gene, rs2275913 (G197A), was found to be associated with the susceptibility of rheumatoid arthritis in the Norwegian population 38 as well as that of ulcerative colitis in the Japanese population. 36 The finding that GVHD mimics some aspects of autoimmune diseases prompted us to investigate the impact of donor and recipient SNPs in the IL-17 gene (rs2275913, G197A) on the clinical outcomes in patients following allogeneic myeloablative BMT using an HLA allele-matched unrelated donor.…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38][39] The promoter SNP of the IL-17 gene, rs2275913 (G197A), was found to be associated with the susceptibility of rheumatoid arthritis in the Norwegian population 38 as well as that of ulcerative colitis in the Japanese population. 36 The finding that GVHD mimics some aspects of autoimmune diseases prompted us to investigate the impact of donor and recipient SNPs in the IL-17 gene (rs2275913, G197A) on the clinical outcomes in patients following allogeneic myeloablative BMT using an HLA allele-matched unrelated donor. The data herein show that the presence of the 197A allele in the recipient is associated with a significantly higher incidence of acute GVHD.…”
Section: Introductionmentioning
confidence: 99%
“…Espinoza et al (17) showed that the IL-17A 197A allele correlates to more efficient IL-17 production. IL-17A (-197A/G) gene polymorphism has been shown to have an effect on the development of ulcerative colitis, gastric carcinogenesis, and acute myeloid leukemia (18)(19)(20).…”
mentioning
confidence: 99%